Ibrahim Ibn Yaqub's Account of His Travel to Slavic Countries As Transmitted by Al-Bakri : With Contemporary Commentaries Edited by Mustafa Switat. - Switat, Mustafa. (Studies in East Asian Literatures and Cultures Series, 2022)
The book provides new findings regarding the social, economic, and political development of the entire Slavic world in the early middle ages based on a critical edition of Ibrāhīm ibn Yaʿqūb's account of his trip to Slavic countries as transmitted by Al-Bakri.